Synthesis Interference of Indonesian Language in the Right of German - Agus Syahid; Muhammad Zaki Pahrul Hadi (Universitas Pendidikan Mandalika, 2019)
Interference is a symptom of irregularities in language rules. It’s can be happend to someone who is learning a foreign language such as students of STIBA Bumigora grade 2015 who learn German as the second foreign language. Language Interference consists of phonological, lexical, morphological, and syntactic interference. In this study, the authors limit his research only to syntactic interference. Syntactic interference consists of two things, they are inter-language interference and intra-language interference. The method of this study is descriptive analysis. The results of the study show us there are several factors that cause errors in syntactic interference on students german essays STIBA Bumigora Mataram. They are; (1) Errors caused by inter-language interference, it's because of the influence of Indonesian language into the German sentence structure. such as; misplaced words and omission of auxilary verb (to be). (2) Errors caused by intra-language interference, it’s because lack of understanding German grammar rules to german essays. Such as; case errors (nominativ, akkusativ, dativ) and verb conjugation errors.